Regulation of different human NFAT isoforms by neuronal activity - Vihma, Hanna; Luhakooder, Mirjam; Pruunsild, Priit; Timmusk, Tõnis (Journal of neurochemistry, 2016)
Nuclear factor of activated T-cells (NFAT) is a family of transcription factors comprising four calcium-regulated members: NFATc1, NFATc2, NFATc3, and NFATc4. Upon activation by the calcium-dependent phosphatase calcineurin (CaN), NFATs translocate from cytosol to the nucleus and regulate their target genes, which in the nervous system are involved in axon growth, synaptic plasticity, and neuronal survival. We have shown previously that there are a number of different splice variants of NFAT genes expressed in the brain. Here, we studied the subcellular localizations and transactivation capacities of alternative human NFAT isoforms in rat primary cortical or hippocampal neurons in response to membrane depolarization and compared the induced transactivation levels in neurons to those obtained from HEK293 cells in response to calcium signaling. We confirm that in neurons the translocation to the nucleus of all NFAT isoforms is reliant on the activity of CaN. However, our results suggest that both the regulation of subcellular localization and transcriptional activity of NFAT proteins in neurons is isoform specific. We show that in primary hippocampal neurons NFATc2 isoforms have very fast translocation kinetics, whereas NFATc4 isoforms translocate relatively slowly to the nucleus. Moreover, we demonstrate that the strongest transcriptional activators in HEK293 cells are NFATc1 and NFATc3, but in neurons NFATc3 and NFATc4 lead to the highest induction, and NFATc2 and NFATc1 display isoform-specific transcription activation capacities. Altogether, our results indicate that the effects of calcium signaling on the action of NFAT proteins are isoform-specific and can differ between cell types. We show that the effects of calcium signaling on the action of NFAT proteins are isoform-specific and differ between cell types. Although nuclear localization of all NFAT isoforms in neurons requires calcineurin, the subcellular distributions, neuronal activity-induced nuclear translocation extent and kinetics, and transcription activation capacities of alternative NFAT proteins vary.
Gesehen am 04.06.2020